Solvent effects on the molecular structure of isolated lignins of Eucalyptus nitens wood and oxidative depolymerization to phenolic chemicals. (July 2022) - Rozas, Robinson; Aspée, Nicolás; Negrete-Vergara, Camila; Venegas-Yazigi, Diego; Gutiérrez-Cutiño, Marlen; Moya, Sergio A.; Zúñiga, César; Cantero-López, Plinio; Luengo, Jorge; Gonzalez, Raúl; Romero, Julio; Yáñez-S, Mauricio
Highlights: In all alkaline oxidations of organosolv lignins, syringaldehyde was obtained as a main product. Oxidation of kraft lignin give rise to lower content the syringaldehyde, this might be due to higher proportion of condensed structures. There is a relationship between β-O-4 linkages content and vanillin yield. After oxidation, residual organosolv lignin decreases its content of condensed phenolic units and increases the content of carboxylic groups. Abstract: The aim of the present work was to study the effect of a solvent/water mixture on the structural characteristics of extracted lignin from Eucalyptus nitens, and to relate the functional groups and interunit linkages present in the lignin with the distribution of phenolic compounds obtained after its alkaline oxidation. The high content of β-O-4′ substructures linked to a S unit in organosolv lignins of E. nitens lignin could be linked to the high yield of syringaldehyde in its alkaline oxidation. Kraft lignin oxidation gives rise to lower content of syringaldehyde when compared with organosolv lignins. This might be due to the higher proportion of condensed structures, mainly β-β´ (∼42%) and spirodienone (∼14%). Fukui functions showed that the regions with higher probability for an electrophilic attack on lignin would be located on phenyl rings and on the phenolic –OH group (benzylic position), whereas nucleophilic attacks in some cases were located over the double bond and ring. This work contributed to a better description of the proposed oxidative depolymerization mechanisms.